An improved stability condition for Kalman filtering with bounded Markovian packet losses - Wu, Junfeng; Shi, Ling; Xie, Lihua; Johansson, Karl Henrik (Automatica (Oxford), 2015)
In this paper, we consider the peak-covariance stability of Kalman filtering subject to packet losses. The length of consecutive packet losses is governed by a time-homogeneous finite-state Markov chain. We establish a sufficient condition for peak-covariance stability and show that this stability check can be recast as a linear matrix inequality (LMI) feasibility problem. Compared with the literature, the stability condition given in this paper is invariant with respect to similarity state transformations; moreover, our condition is proved to be less conservative than the existing results. Numerical examples are provided to demonstrate the effectiveness of our result.